Influência da anodização pulsada nas propriedades da alumina anódica porosa (AAP) - Santos, Caio Guilherme Pereira dos (2017)
Porous anodic alumina can be obtained, in addition to conventional methods such as potentiostatic and galvanostatic, or by pulsed method. Among these are the methods of discontinuous pulse, hybrid pulse and polarized pulse methods. The structures formed by these methods can be applied to sensors and photonic materials. In this work the influences of the pulse parameters for the porous anodic alumina were investigated by polarized pulse potentiostatic anodization. Data analysis was presented from the duty cycle seen in the literature, which provides important information about the structure formed for the applied conditions and, in addition, new ways of analyzing the data related to the pulse, such as the analysis of the potential difference and the pulse frequency, this latter complementing the analysis of the duty cycle. As a result it was possible to observe that the porous anodic alumina thickness obtained is proportional to the duty cycle applied, where the higher duty cycle, the greater the thickness obtained. From the potential difference, the differences in the morphological and optical parameters could be analyzed by the influence of the negative minimum voltage applied during the pulsed anodization. The pulse frequency, also discussed in this work, was used to analyze different pulse periods for the same duty cycle, demonstrating that can be obtained structures with different values by varying the value of the pulse frequency. For the porosity calculation, an application was developed that helped to obtain the pore distance, which is one of the variables used to calculate the porosity. With the porosity values, the effective refractive index of each sample was calculated to find the effective optical thickness (EOT) and, finally, the thickness of the obtained anodic alumina film.